The EphB6 receptor is overexpressed in pediatric T cell acute lymphoblastic leukemia and increases its sensitivity to doxorubicin treatment. Issue 1 (December 2017) - El Zawily, Amr; McEwen, Emily; Toosi, Behzad; Vizeacoumar, Frederick; Freywald, Tanya; Vizeacoumar, Franco; Freywald, Andrew
Abstract While impressive improvements have been achieved in T-ALL therapy, current treatment approaches fail in approximately 25% of patients and these patients have limited treatment options. Another significant group of patients is being overtreated, which causes long-lasting side effects. Identification of molecules controlling drug resistance in T-ALL is crucial for treatment optimisation in both scenarios. We report here the EphB6 receptor is frequently overexpressed in T-ALL. Remarkably, our observations indicate that EphB6 acts in T-ALL cells to enhance sensitivity to a DNA-damaging drug, doxorubicin, as interruption of EphB6 activity interferes with the efficiency of doxorubicin-induced eradication of T-ALL cells in cell culture and in xenograft animals. This effect relies on the protection of Akt kinase signaling, while Akt inhibition combined with doxorubicin application produces synergistic effects on the elimination of EphB6-deficient T-ALL cells. These data imply that EphB6 suppresses T-ALL resistance by interfering with Akt activity. Our observations highlight a novel role for EphB6 in reducing drug resistance of T-ALL and suggest that doxorubicin treatment should produce better results if personalised based on EphB6 levels. If successfully verified in clinical studies, this approach should improve outcomes for T-ALL patients resistant to current therapies and for patients, who are being overtreated.